2014
DOI: 10.1080/10298436.2014.968570
|View full text |Cite
|
Sign up to set email alerts
|

A model for equivalent axle load factors

Abstract: Most design methods for road pavements require the design traffic, based on the transformation of the traffic spectrum, to be calculated into a number of equivalent passages of a standard axle using the equivalent axle load factors (EALFs). In general, these factors only consider the type of axle (i.e. single, tandem or tridem), but they do not consider the type of wheel on the axles, i.e. single or dual wheel. The type of wheel has an important influence on the calculation of the design traffic. The existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…The bearing capacity of pavement is defined as a characteristic of its structural state, related to the capacity to support the expected traffic. The evaluation of this capacity can be made through parameters such as residual life, required thickness for reinforcement, stiffness modulus and deflection [2].…”
Section: Introductionmentioning
confidence: 99%
“…The bearing capacity of pavement is defined as a characteristic of its structural state, related to the capacity to support the expected traffic. The evaluation of this capacity can be made through parameters such as residual life, required thickness for reinforcement, stiffness modulus and deflection [2].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation was carried out on Indonesia's national highways, and Table 1 presents the prescribed upper limit for the load capacity of each truck category. The data on a load of heavy vehicles was converted into the equivalent standard axle load (ESAL) using the model developed by [22,23], which will be combined to obtain the Truck Factor for each vehicle and then calculate how this damage affects the flexible pavement using equation (1):…”
Section: Methodsmentioning
confidence: 99%
“…Amorim et al [7] reported a multi-layer perceptron neural network (MLPNN) with two concealed layers for determining the ratio of the influence of various configurations of axle loads. Since the existing mechanical-empirical equation is very complicated for the design equivalent single axle load (ESAL) evaluation, an ANN was developed for the computation of EALFs.…”
Section: Flexible Pavement Performancementioning
confidence: 99%